Anti-Inflammatory Activity of APPA (Apocynin and Paeonol) in Human Articular Chondrocytes - Mercedes Fernández-Moreno; Tamara Hermida-Gómez; Nicholas Larkins; Alan Reynolds; Francisco J. Blanco (MDPI AG, 2024)
Osteoarthritis (OA) is a chronic joint disease leading to cartilage loss and reduction in the joint space which results in pain. The current pharmacological treatment of OA is inadequate and pharmacological interventions focus on symptom management. APPA, a combination of apocynin (AP) and paeonol (PA), is a potential drug for treating OA. The aim of this study was to analyze the effects of APPA on the modulation of the inflammatory response in chondrocytes. Samples were incubated with IL-1β and APPA, and their responses to proinflammatory cytokines, catabolic mediators and redox responses were then measured. The effect of APPA on mitogenesis was also evaluated. Results show that APPA attenuated the expression of IL-8, TNF-α, MMP-3, MMP-13, SOD-2 and iNOS, resulting in the protection of human articular cartilage. APPA decreased PGC-1α gene expression induced by IL-1β. APPA did not modulate the gene expression of Mfn2, Sirt-1 or Sirt-3. The overall findings indicate that APPA may be an effective treatment for OA by targeting several of the pathways involved in OA pathogenesis.